Building the family nest: pre-marital investments, marriage markets and spousal allocations - Murat Iyigun; Randall P. Walsh (Institute for the Study of Labor (IZA), 2005)
We develop a model of the household in which spousal incomes are determined by pre-marital investments, the marriage market is characterized by assortative matching, and endogenously-determined sharing rules form the basis of intra-household allocations. By incorporating pre-marital investments and spousal matching into the collective household model, we are able to identify the fundamental determinants of endogenously determined and maritally sustainable intra-marital sharing rules. In particular, we find that all sharing rules along the assortative order support unconditionally efficient outcomes where both pre-marital investments and intra-household allocations are efficient. The efficiency of both pre-marital choices and household allocations then enables us to show that, for each couple, the marriage market generates a unique and maritally sustainable sharing rule that is a function of the distribution of pre-marital endowments and the sex ratios in the market.
Keywords: C78; D61; D70; 330; collective model; marriage; bargaining; household labor supply; Familienökonomik; Ehe; Matching; Arbeitsangebot